2010
DOI: 10.3233/oer-2010-0178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vibration push force, exposure duration and working posture on operators performing a grinding task

Abstract: It has been shown that vibration level, push force, exposure duration and working posture cause unfavorable effects on the work performance when hand held vibrating tools are used by operators. The present study analyzed the effects of these variables on the heart rate and systolic blood pressure of the operators carrying out a manual-grinding task. Four levels of vibration (12.5, 13.6, 14.8 and 18 m/s2), three levels of push force (5, 10, 15 N), three levels of working posture (180°, 150° and 120° elbow flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A total of 36 studies were considered suitable for full‐text appraisal. Of these, 14 studies (Goodwin et al ., ; Jennings et al ., ; Rittweger et al ., ; Madhavan et al ., ,b; Mester et al ., ; Mileva et al ., ; Da Silva et al ., ; Lohman et al ., ; Cochrane et al ., ; Otsuki et al ., ; Zheng et al ., ; Muzammil et al ., ; Figueroa et al ., ) were excluded with reasons provided in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 studies were considered suitable for full‐text appraisal. Of these, 14 studies (Goodwin et al ., ; Jennings et al ., ; Rittweger et al ., ; Madhavan et al ., ,b; Mester et al ., ; Mileva et al ., ; Da Silva et al ., ; Lohman et al ., ; Cochrane et al ., ; Otsuki et al ., ; Zheng et al ., ; Muzammil et al ., ; Figueroa et al ., ) were excluded with reasons provided in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…Deterioration of handgrip capacity is an indication of the development of musculoskeletal diseases of the upper extremity [40]. Several studies [41][42][43] have shown that workers subjected to vibratory hand tools suffer from pain, muscle weakness, resulting in musculoskeletal disorders due to diminished grip ability, fatigue, and reduced performance.…”
Section: Discussionmentioning
confidence: 99%
“…Upright postures and angle grinders with as little weight as possible result in the lowest disc pressures and low recovery times. A study on the superposed loads of work tasks, posture, vibration, and work duration is available from Muzammil M, et al [7]. Using 30 male subjects, blood pressure and heart rate were examined.…”
Section: Overview Of Technical and Ergonomic Angle Grinder Studiesmentioning
confidence: 99%